Analisis Penerimaan Aplikasi Samsat Digital Nasional dengan Menggunakan Mobile Technology Acceptance Mode - Ardianda, Feri; Ruliansyah, Ruliansyah; Alfresi, Aminullah Imal (Journal of Informatics Management and Information Technology, 2025)
The rapid development of technology requires the government, including the One-Stop Integrated Administration System (SAMSAT), to integrate technology into their services. The One-Stop Integrated Administration System (SAMSAT), has developed various systems, one of which is the National Digital Samsat (SIGNAL). However, the implementation of this system brings concerns regarding user acceptance. The study was conducted to determine the level of acceptance and what factors influence the SIGNAL application at Samsat UPTB 1 Palembang using MTAM (Mobile Technology Accepted Model). This study uses a descriptive quantitative method with data collection methods that will be carried out, namely through interview techniques, questionnaires, and observation. The population and sample in this study are active SIGNAL users at Samsat UPTB 1 Palembang with a simple random sampling technique. The population of SIGNAL users is 9335, so the sample calculated using the Slovin formula, assuming a 95% reliability level, obtained a sample of 384 respondents. Data analysis used PLS-SEM with the Smart-PLS 4 tool. The results of the study showed that the level of acceptance of the SIGNAL application by the community at Samsat UPTB 1 Palembang was classified as accepting, with an average value of 3.23 from 384 respondents. Based on the MTAM analysis, it was found that the variables Mobile Usefulness and Mobile Perceived Financial Resources had a positive effect on Behavioral Intention, while Mobile Ease of Use had a negative effect. On the other hand, the variables Mobile Perceived Compatibility, Mobile Perceived Security Risk, and Mobile Perceived Trust did not show any effect on Behavioral Intention. In addition, Mobile Perceived Compatibility had a negative effect on Mobile Usefulness, while Mobile Perceived Financial Resources had a positive effect on Mobile Usefulness. As for Mobile Ease of Use, only Mobile Perceived Financial Resources had a positive effect, while Mobile Perceived Compatibility had no effect.